2020
DOI: 10.1164/rccm.201911-2169oc
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Fluid suPAR Levels Predict the Need for Invasive Management in Parapneumonic Effusions

Abstract: Rationale: Parapneumonic effusions have a wide clinical spectrum. The majority settle with conservative management but some progress to complex collections requiring intervention. For decades, physicians have relied on pleural fluid pH to determine the need for chest tube drainage despite a lack of prospective validation and no ability to predict the requirement for fibrinolytics or thoracic surgery.Objectives: To study the ability of suPAR (soluble urokinase plasminogen activator receptor), a potential biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…High affinity binding to its ligand, uPA, primarily involves domain I, while requiring the structural integrity of all three domains [ 86 ]. Although a splice variant of the PLAUR gene can generate a soluble uPAR construct [ 87 ], soluble uPAR is also generated by cleavage of cell-surface uPAR and occurs in serum and other biologic fluids, including pleural effusions [ 88 , 89 ]. suPAR can be generated by cleavage of the GPI-anchor of uPAR at the cell surface by enzymes such as phospholipase C [ 90 ].…”
Section: The Role Of Soluble Upar In Pleural Injury: Biomarker Efmentioning
confidence: 99%
See 1 more Smart Citation
“…High affinity binding to its ligand, uPA, primarily involves domain I, while requiring the structural integrity of all three domains [ 86 ]. Although a splice variant of the PLAUR gene can generate a soluble uPAR construct [ 87 ], soluble uPAR is also generated by cleavage of cell-surface uPAR and occurs in serum and other biologic fluids, including pleural effusions [ 88 , 89 ]. suPAR can be generated by cleavage of the GPI-anchor of uPAR at the cell surface by enzymes such as phospholipase C [ 90 ].…”
Section: The Role Of Soluble Upar In Pleural Injury: Biomarker Efmentioning
confidence: 99%
“…In a recent study, pleural fluid suPAR levels were found to correlate with the requirement for invasive management in parapneumonic pleural effusions [ 89 ]. This work extends prior work showing that elevated levels of suPAR occur in a range of biologic fluids in infectious, autoimmune and neoplastic diseases, as previously reviewed [ 88 ].…”
Section: The Role Of Soluble Upar In Pleural Injury: Biomarker Efmentioning
confidence: 99%
“…In the context of pleural infection, PF soluble urokinase Plasminogen Activator Receptor (suPAR) has been shown to be potentially of use in predicting the need for tube thoracostomy in parapneumonic effusions, though prospective validation in a multicentre trial setting is awaited [33].…”
Section: Pleural Fluid Biochemistrymentioning
confidence: 99%
“…While patient mortality is negligible, the rate of IPFT failure in pediatric empyema remains around 15% ( Sonnappa et al, 2006 ; St Peter et al, 2009 ; Livingston et al, 2016b ; Long et al, 2016 ; Derderian et al, 2020 ). Defining reliable molecular predictors of treatment failure ( Arnold et al, 2012020 ; Derderian et al, 2020 ; Khemasuwan et al, 2018 ; Livingston et al, 2016a ) would therefore likely increase the efficacy of IPFT as a therapy for empyema in pediatrics. The striking difference in the efficacy of IPFT in adult and pediatric patients with empyema abrogates the possibility of applying successful pediatric treatments to adults.…”
Section: A Call For Novel Approaches To Assess the Likelihood Of Success Of Ipftmentioning
confidence: 99%